2020
DOI: 10.13057/biodiv/d211005
|View full text |Cite
|
Sign up to set email alerts
|

Selection of stain fungi on rubberwood (Hevea brasiliensis) and its growth response against chitosan

Abstract: Abstract. Salman ABA, Sudirman LI, Nandika D. 2020. Selection of stain fungi on rubberwood (Hevea brasiliensis) and its growth response against chitosan. Biodiversitas 21: 4501-4508. Rubberwood (Hevea brasiliensis Muell. Arg.) is one of the most important raw materials in furniture industry in South East Asian countries, particularly in Indonesia, Thailand and Malaysia. However, due to its susceptibility to stain fungi attack, wood preservative is needed to processing this material, which has both significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…The is discoloration influenced by melanin crystallization around hyphae or from secretion of extracellular material [17]. Salman et al [18] reported that Aspergillus foetidus caused the worst discoloration on air-dried rubberwood, which is processed for furniture products in West Java Province, Indonesia. The growth rate of fungus on the wood surface reached 90.5%.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The is discoloration influenced by melanin crystallization around hyphae or from secretion of extracellular material [17]. Salman et al [18] reported that Aspergillus foetidus caused the worst discoloration on air-dried rubberwood, which is processed for furniture products in West Java Province, Indonesia. The growth rate of fungus on the wood surface reached 90.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in the rainy season, rainwater containing nutrients wets the wood, thus promoting biodeterioration activities of fungi [23]. In 2018, economic loss due to stain fungi attacks on rubberwood raw material in Indonesian furniture industry alone reached almost USD 15,246 million [18]. In fact, this economic loss is higher than the value since others light-color wood species used in the furniture industry were also susceptible to stain fungi.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that three stain fungi species were identified from rubberwood, which were Aspergillus niger, Aspergillus flavus, and Penicillium citrinum (Oldertrøen et al 2016). Meanwhile, Salman et al (2020) reported that at least there were two stain fungi isolated from air dried rubberwood which will be processed for furniture products in West Java Province, Indonesia, which were Aspergillus aflatoxiformans and A. foetidus. In addition, Razali et al (2016) reported that there were seven isolates obtained from rubberwood and classified into three groups, namely Fusarium equiseti, Mucor irregularis, and Lasiodiplodia theobromae.…”
Section: Introductionmentioning
confidence: 99%